M2 Using a Transportable Oxygen Concentrator (TPOC) to facilitate prompt and safe hospital discharge. (12th November 2015) - Hamilton, F; Luxford, G; Bott, J
Abstract : Introduction: Whilst current guidelines 1 state that patients must be clinically stable prior to commencing home oxygen, respiratory patients can be discharged with a supply of oxygen. Multiple errors are often found on the Home Oxygen Order Forms (HOOFs) for hospital discharges and equipment requirements are often subsequently changed, generating wasteful activity and costs. The aim was to establish whether a TPOC could be provided to specialist respiratory teams within hospitals to promote efficient and safe discharge for those patients requiring home oxygen. Method: Three hospitals with established Home Oxygen Assessment and Review Services (HOSAR) were issued with TPOCs. The Home Oxygen Supplier trained the HOSAR clinicians on use, and supplied written documentation on safety. The clinicians identified appropriate patients based on clinical assessments and issued them with a TPOC. A HOOF was then sent to the supplier with appropriate equipment for the patient's long term needs. On installation of this, the supplier removed the TPOC and another was issued to the hospital to enable an ongoing supply. Results: Of those discharged with a TPOC and a subsequent HOOF, only 5% (n = 6) of patients required a modality change or HOOF update within the following month, compared to 40% (n = 33296) of all other HOOFs received (Figure 1 ). The largest group of patients issued with a TPOC on discharge were clinically coded as COPD (40%), followed by those coded as Palliative Care (28%). Conclusion: The results demonstrate the practical uses of a TPOC for hospital discharge in clinically appropriate patients and a greater degree of control over the accuracy of ordering. A precise cost saving cannot be demonstrated as it is unclear how many bed days were saved, but it is clear that a reduction in wasteful activity by more accurate ordering would have reduced costs. Discussion: By using staff trained on equipment and accurately completing HOOFs, combined with equipment readily available, transition from hospital to home can be both clinically accurate, time efficient and cost effective. Reference: 1 Hardinge M, Annandale J, Bourne S, et al . British Thoracic Society guidelines for home oxygen use in adults. Thorax 2015;70 :i1–i43